Oxygen electrochemistry in Li‐O2 batteries probed by in situ surface‐enhanced Raman spectroscopy. Issue 3 (30th August 2021) - Wang, Jiawei; Ma, Lipo; Xu, Junyuan; Xu, Ye; Sun, Ke; Peng, Zhangquan
Abstract: Surface‐enhanced Raman spectroscopy (SERS), as a nondestructive and ultra‐sensitive single molecular level characterization technique, is a powerful tool to deeply understand the interfacial electrochemistry reaction mechanism involved in energy conversion and storage, especially for oxygen electrochemistry in Li‐O2 batteries with unrivaled theoretical energy density. SERS can provide precise spectroscopic identification of the reactants, intermediates and products at the electrode|electrolyte interfaces, independent of their physical states (solid and/or liquid) and crystallinity level. Furthermore, SERS's power to resolve different isotopes can be exploited to identify the mass transport limitation and reactive sites of the passivated interface. In this review, the application of in situ SERS in studying the oxygen electrochemistry, specifically in aprotic Li‐O2 batteries, is summarized. The ideas and concepts covered in this review are also extended to the perspectives of the spectroelectrochemistry in general aprotic metal‐gas batteries. Abstract : In situ surface‐enhanced Raman spectroscopy (SERS), as a nondestructive and ultra‐sensitive single molecular level characterization technique, has become one of the favorite tools for the characterization of the interfaces in diverse electrochemical energy storage and conversion systems, notably the Li‐O2 batteries. In this review, we summarized what SERS has accomplished on the understanding of the reaction pathways, reactive sites, and parasitic reaction mechanism essential to the oxygen electrochemistry (OER and ORR) in aprotic Li‐O2 batteries. Both the latest understanding of the reaction mechanism and the rationales underlying the experiment design are given the equal amount of emphasis.